PREVALENCE OF ARTERIAL HYPERTENSION AND RISK FACTORS IN YOUNG ADULTS - N. T. Vatutin; E. V. Sklyanna (Архивъ внутренней медицины)
Arterial hypertension (AH) is one of the most widespread diseases in whole the world. AH in youth is associated with high cardiovascular mortality in middle age.Objectives: The study objectives were to studied prevalence of AH and risk factors in young adults.Methods. We studied prevalence of AH and risk factors in 981 young adults aged 20-29 years old (22,3 ± 2,26) in cross-sectional epidemiological study.Results. Prevalence of AH was 14,2%, it was significantly higher in men (22,2%) then in women (4,5%), p>0,05. There was a high prevalence of AH risk factors: overweight (35,4% in men), smoking (27,8% in men), parental hypertension (57,8%), noncompliance of day regimen (58,8%), high stress level (37,7%). In AH group prevalence of overweight, smoking, high salt consumption, parental hypertension and hypodinamia was significantly higher than in population.Conclusions. Prevalence of AH was 14,2%, main risk factors of AH were observed in more then quarter of studied persons.